ISOLASI, IDENTIFIKASI DAN KARAKTERISASI Vibrio spp. PATOGEN PENYEBAB VIBRIOSIS PADA KERAPU DI BALAI BUDIDAYA AIR PAYAU SITUBONDO - Kamiso Handoyo Nitimulyo; Alim Isnansetyo; Triyanto Triyanto; Indah Istiqomah; Muhammmad Murdjani (Jurnal Perikanan Universitas Gadjah Mada, 2005)
This research was conducted to isolate, identify, and characterize pathogenic Vibrio spp., causative agents of vibriosis in grouper at Brackishwater Aquaculture Development Center (BADC), Situbondo. Twenty-nine isolates were isolated from wound, gills, eyes, liver, and ren of grouper with vibriosis on Thiosulphate Citrate Bile Sucrose Agar (TCBSA) medium. Koch Postulate Test was conducted to determine pathogenic Vibrio spp., by intraperitoneal injection to humpback grouper (Cromileptes altivelis) (9-10 cm of total length) at 106 cells/fish in triplicates. Results indicated that the pathogenic Vibrio spp., causative agents of vibriosis in grouper at BADC, Situbondo were identified to be V. alginolyticus, V. anguillarum, V. metchnikovii, V. vulnificus, V. fluvialis, V. furnisii, and V. parahaemolyticus. Infection of the pathogenic Vibrio spp. caused acute mortality within 17-46 hours with specific disease signs like haemorhagic on fins (pinnae pectorales, pinnae abdominales, pinna analis) and also on the body. These results suggested that vibriosis should be monitored and controlled properly and quickly.